Branching Pattern of the Cerebral Arterial Tree. Issue 8 (5th December 2018) - Helthuis, Jasper H. G.; van Doormaal, Tristan P. C.; Hillen, Berend; Bleys, Ronald L. A. W.; Harteveld, Anita A.; Hendrikse, Jeroen; van der Toorn, Annette; Brozici, Mariana; Zwanenburg, Jaco J. M.; van der Zwan, Albert
ABSTRACT: Quantitative data on branching patterns of the human cerebral arterial tree are lacking in the 1.0–0.1 mm radius range. We aimed to collect quantitative data in this range, and to study if the cerebral artery tree complies with the principle of minimal work (Law of Murray). To enable easy quantification of branching patterns a semi‐automatic method was employed to measure 1, 294 bifurcations and 2, 031 segments on 7 T‐MRI scans of two corrosion casts embedded in a gel. Additionally, to measure segments with a radius smaller than 0.1 mm, 9.4 T‐MRI was used on a small cast section to characterize 1, 147 bifurcations and 1, 150 segments. Besides MRI, traditional methods were employed. Seven hundred thirty‐three bifurcations were manually measured on a corrosion cast and 1, 808 bifurcations and 1, 799 segment lengths were manually measured on a fresh dissected cerebral arterial tree. Data showed a large variation in branching pattern parameters (asymmetry‐ratio, area‐ratio, length‐radius‐ratio, tapering). Part of the variation may be explained by the variation in measurement techniques, number of measurements and location of measurement in the vascular tree. This study confirms that the cerebral arterial tree complies with the principle of minimum work. These data are essential in the future development of more accurate mathematical blood flow models. Anat Rec, 302:1434–1446, 2019. © 2018 The Authors. The Anatomical Record published by Wiley Periodicals, Inc. on behalf of American Association of Anatomists.